Potential use of Purslane (Portulaca oleracea L.) as alternative wound healing therapy - Setyowati, Hanny (Cermin Dunia Kedokteran, 2017)
Portulaca oleraceae (Indonesian name: Krokot) is a herbaceous succulent annual plant, distributed in tropical region. Chemical constituents such as flavonoids, alkaloids, fatty acids, terpenoids, polysaccharides, vitamins, sterols, proteins, and minerals have been isolated from this plant. The pharmacological properties, based on scientific research, are claimed as antibacterial, antiulcerogenic, anti-inflammatory, antioxidant, and especially for wound-healing. Triterpenoids and flavonoids play an important role, promotes wound contraction and increases epithelialization rate in the wound-healing process.Portulaca oleraceae (nama Indonesia: Krokot) adalah tumbuhan perdu sepanjang musim, tersebar di daerah tropis. Senyawa kimia seperti flavonoid, alkaloid, asam lemak, terpenoid, polisakarida, vitamin, sterol, protein, dan mineral telah diisolasi dari tanaman ini. Aktivitas farmakologis, berdasarkan hasil penelitian, dilaporkan sebagai antibakteri, antiulkus, antiinflamasi, antioksidan, dan terutama untuk penyembuhan luka. Triterpenoid dan flavonoid memiliki peran penting, yakni menstimulasi penyempitan bekas luka dan mempercepat penutupan luka.